2020
DOI: 10.1371/journal.pone.0242301
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing inter-reader variability affecting deep ensemble learning for COVID-19 detection in chest radiographs

Abstract: Data-driven deep learning (DL) methods using convolutional neural networks (CNNs) demonstrate promising performance in natural image computer vision tasks. However, their use in medical computer vision tasks faces several limitations, viz., (i) adapting to visual characteristics that are unlike natural images; (ii) modeling random noise during training due to stochastic optimization and backpropagation-based learning strategy; (iii) challenges in explaining DL black-box behavior to support clinical decision-ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 41 publications
0
37
1
Order By: Relevance
“…Based on the used X-ray datasets, several studies differentiated the data into two classes of patients with COVID-19 and non-COVID-19 patients [ 21 , 24 , 25 , 29 , 36 , 39 , 40 , 42 , 45 , 46 ]. In others, the database included more than two classes, e.g., viral pneumonia, bacterial pneumonia, and normal and COVID-19 cases [ 17 , 23 , 30 35 , 37 , 39 , 41 , 43 , 47 50 ]. Through the synthesis of the data, four domains of AI applications in X-ray analysis were identified:…”
Section: Resultsmentioning
confidence: 99%
“…Based on the used X-ray datasets, several studies differentiated the data into two classes of patients with COVID-19 and non-COVID-19 patients [ 21 , 24 , 25 , 29 , 36 , 39 , 40 , 42 , 45 , 46 ]. In others, the database included more than two classes, e.g., viral pneumonia, bacterial pneumonia, and normal and COVID-19 cases [ 17 , 23 , 30 35 , 37 , 39 , 41 , 43 , 47 50 ]. Through the synthesis of the data, four domains of AI applications in X-ray analysis were identified:…”
Section: Resultsmentioning
confidence: 99%
“…This is because the transfer of weights from the majority dataset does not adequately generalize on smaller medical datasets. Literature studies have shown that compared to using ImageNet-pretrained CNN models, CXR modality-specific model retraining (i) delivers superior performance toward classifying CXRs as showing normal lungs or other pulmonary abnormal manifestations and (ii) improve ROI localization performance with added benefits of reduced overfitting, prediction variance, and computational complexity [ 17 ]. CXR modality-specific pretraining converts the weight layers specific to the CXR modality and learns relevant features.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies demonstrate improved model robustness and generalization when the knowledge transfer is initiated from medical image modality-specific pretrained CNN models to a relevant medical visual recognition task [ 17 ]. Unlike conventional transfer learning, such a knowledge transfer, has demonstrated superior model adaptation to a relevant target task, particularly when the target task suffers from limited data availability.…”
Section: Introductionmentioning
confidence: 99%
“…Ensembles were explored later in the pandemic, 75,76 including different binary ML classifiers applied to CNN extracted features 77 and multi‑layer perceptron stacked ensembling 78 …”
Section: Automatic Disease Detection On Cxr Imagesmentioning
confidence: 99%